La calidad de la atención médica - Clemente Heimerdinger, Dr. Antonio (Gaceta Médica de Caracas, 2021)
Se definen y relacionan la calidad y la cantidad con la salud. Establecemos el vínculo del trabajo con la ponencia “Evaluación de la atención médica”, presentada en la XLI Asamblea ordinaria anual de la Federación Médica Venezolana en 1986. We define and relate quantity and quality with health. It was established the bond between this paper and the study on evaluation of medical attention, presented in the XLI Assembly of the “Federación Médica Venezolana” 1986.